The Strategy of Islamic Religious Education Teacher in Applying Hidden Curriculum to Increase Student Learning Activeness - Haidir Haidir; Muhammad Alfaridzi Matondang; Chairul Azmi Lubis; Aisyah Siregar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
In accordance with the formulation of the problem, this study aims to find out: PAI teachers 'strategies in implementing the hidden curriculum to increase the learning activity of students, Implementation of the hidden curriculum carried out by teachers to increase students' learning activeness, Barriers faced by teachers in implementing hidden curricula and solutions against the obstacles faced by teachers in implementing the hidden curriculum.The research method used is seen from the type of research is qualitative research, and in the data collection process, the authors use the method of observation, interviews and documentation. As for the analysis, the writer uses a qualitative descriptive analysis, which is in the form of written or oral data from the person or actor being observed so that in this case the writer conducts research that describes the actual situation as a whole. The results of the research conducted indicated that, among others: There was a strategy of Islamic Education teachers in implementing the hidden curriculum to increase the learning activity of students. The implementation of the hidden curriculum carried out by the teacher to increase the learning activeness of students is so diverse. There are obstacles faced by teachers in implementing the hidden curriculumas well, the lack of teacher understanding in the use of IT in the learning process, the lack of facilities and infrastructure in the learning process, the presence of students a little late in the learning process. There are various solutions to the obstacles faced by teachers in implementing the hidden curriculum.